Enhancing Accounting Students' Competencies through Digital Accounting Information System Design - Sahlan, Fahmi; Hajar, Nuzul Ibnu; Pracita, Sriayu (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This study aims to develop a learning model that integrates the ADDIE approach with project-based learning to enhance students' analytical skills and deepen their understanding of accounting concepts. The model focuses on the design of accounting information systems using Excel Visual Basic for Applications (VBA), providing a practical, technology-driven framework for accounting education. The research adopts a Research & Development (R&D) methodology grounded in the ADDIE development model. This model encompasses five key stages: conducting a needs analysis, designing the learning framework, developing materials and learning scenarios alongside Excel VBA applications, implementing the model, and evaluating its effectiveness in achieving learning outcomes. The findings reveal that the project-based learning model for accounting information system design using Microsoft Excel VBA is both valid and effective. It significantly enhances students' understanding and skills in the Accounting Study Program at STIE Enam Enam Kendari. Validation results confirm the high quality of the developed learning model and its potential for effective implementation in accounting education, offering valuable insights for improving teaching and learning processes in similar academic settings.